Transformasi Digital dalam Pembelajaran Pendidikan Agama Islam - Totong Heri; sirdau sisilawati (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
Digital transformation has brought significant changes to various aspects of life, including the education sector and Islamic Religious Education (IRE) learning. The rapid development of digital technologies has fostered innovative learning approaches that are more interactive, flexible, and learner-centered. This study aims to analyze digital transformation in IRE learning and identify the opportunities and challenges of utilizing digital technologies, particularly the Metaverse, to support adaptive learning that aligns with the characteristics of Generation Z. This research employed a qualitative method using a Systematic Literature Review (SLR) approach. Data were collected through documentation studies of relevant scholarly journal articles, books, and academic publications that had undergone a peer-review process. The literature selection process was conducted based on thematic relevance, publication period, and alignment with the research objectives. As a result, five core articles were selected and analyzed using content analysis techniques through coding, categorization, and synthesis of findings. The results revealed four major themes: digital transformation in IRE learning, the implementation of the Metaverse as an interactive learning medium, the enhancement of teachers’ digital literacy, and the application of differentiated learning. The findings indicate that digital technologies have the potential to improve learning quality through greater accessibility, interactivity, personalization, and student engagement. However, their implementation continues to face challenges, including limited digital competencies among educators, inadequate technological infrastructure, and the need to integrate Islamic values into technology use. This study contributes to the advancement of digital-based Islamic education research and serves as a reference for educational policy development and innovation in IRE learning in the era of digital transformation.